LABOUR MIGRATION AND INTEGRATION IN KERALA - Jonathon W. Moses and S. Irudaya Rajan (Labour & Development, 2012)
This article employs survey data from the most recent Inter-State Migrant Survey in Kerala (ISMSK) to show how out-of-state migrants are kept isolated from the surrounding community. Migrant workers to Kerala are unable to integrate with local workers and residents to gain important information about local wage levels, worker rights and working standards. Worse, local labour unions are not trying to integrate these workers into the labour market or inform them about local conditions. This lack of integration poses a long-term threat to the strength and viability of the Keralite labour movement, and the larger social model in which it is embedded.